2018
DOI: 10.1111/cas.13662
|View full text |Cite
|
Sign up to set email alerts
|

Yin Yang 1 promotes the Warburg effect and tumorigenesis via glucose transporter GLUT3

Abstract: Cancer cells typically shift their metabolism to aerobic glycolysis to fulfill the demand of energy and macromolecules to support their proliferation. Glucose transporter (GLUT) family‐mediated glucose transport is the pacesetter of aerobic glycolysis and, thus, is critical for tumor cell metabolism. Yin Yang 1 (YY1) is an oncogene crucial for tumorigenesis; however, its role in tumor cell glucose metabolism remains unclear. Here, we revealed that YY1 activates GLUT3 transcription by directly binding to its pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…It has been indicated that YY1 acts as an important transcription factor to affect critical gene expression. For example, YY1 promotes tumorigenesis via regulating glucose transporter GLUT3 27 . YY1 enhances G6PD transcription and directly activates the pentose phosphate pathway to accelerate cell proliferation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that YY1 acts as an important transcription factor to affect critical gene expression. For example, YY1 promotes tumorigenesis via regulating glucose transporter GLUT3 27 . YY1 enhances G6PD transcription and directly activates the pentose phosphate pathway to accelerate cell proliferation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…YY1 can function as transcription factor and plays an important regulatory role in various biological processes by binding to DNA and numerous proteins, consequently impacting the pathologic processes of cancers [19][20][21][22]. YY1 has been reported to induce lncRNA MCM3AP-AS1 overexpression in lung cancer, and overexpressed MCM3AP-AS1 promoted angiogenesis via targeting KPNA4 through shared miR-340-5p [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental studies have demonstrated its role in the silencing of oxidative phosphorylation and switching to aerobic glycolysis [ 53 ]. Additionally, an oncogenic transcription factor, Yin Yang 1 (YY1), promotes aerobic glycolysis via upregulation of GLUT3 [ 54 ].…”
Section: Molecular View Into the Warburg Effectmentioning
confidence: 99%